Accidental subdural anesthesia after epidural puncture: case report ocurred at a university hospital - Horner, Christine (2024)
Epidural anesthesia is a procedure performed worldwide due to its safety and benefits offered to surgical patients. The subdural space is a virtual space that is located between the arachnoid and the dura mater. Accidental punctures in this space are rare to occur. The objective of this article is to report a case of accidental subdural anesthesia during a surgical procedure to correct an epigastric hernia at a University Hospital located in the interior of Rio Grande do Sul in 2023. The patient in question evolved as expected according to the chosen anesthetic technique. As the surgery progressed, the patient developed desaturation, decreased level of consciousness, and orotracheal intubation was performed. At the end of the procedure, the patient was sent to the Post-Anesthetic Recovery Room (PACU) intubated, on mechanical ventilation and with adequate sedoanalgesia. The patient maintained all vital parameters stable, with low ventilatory parameters and without the need of vasoactive drugs. After an hour and a half, extubation was performed without any type of complications. The hypothesis of subdural block was raised due to the occurrence of intense sensory and motor block, with negative liquor aspiration and late onset of the block. Appropriate anesthetic management was instituted according to the patient’s needs (in addition to basic intraoperative monitoring, orotracheal intubation and mechanical ventilation, consciousness monitoring and neuromuscular blockade were performed). Although subdural block is a very uncommon event in epidural anesthesia, it can occur and early recognition and appropriate management are fundamental.